2020
DOI: 10.4143/crt.2019.593
|View full text |Cite
|
Sign up to set email alerts
|

CXCL-13 Regulates Resistance to 5-Fluorouracil in Colorectal Cancer

Abstract: Purpose5-Fluorouracil (5-Fu) is used as a conventional chemotherapy drug in chemotherapy for patients with advanced colorectal cancer, but many patients still suffer from treatment failure due to 5-Fu resistance. Emerging observations revealed the important role of chemokine (C-X-C motif) ligand 13 (CXCL-13) in tumor microenvironment and its relationship with prognosis in patients with colorectal cancer. This study is designed to reveal the important role of CXCL-13 in causing colorectal cancer resistance to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…The significance of TME in mediating 5-FU drug resistance has also gained attention in recent years due to its crosstalk influence on tumor cell behavior. For instance, in one study, chemokine C-X-C motif ligand 13 (CXCL-13) is found highly-expressed in the TME of 5-FU-resistant colon cancer cells as well as in sera of 5-FU-resistant patients associated with worse clinical outcome [ 145 ]. Although the mechanism as to how CXCL-13 participates in 5-FU resistance was not stated, it is highly plausible that resistance is achieved through piggybacking the same pathways responsible in promoting tumor growth, migration, and invasion in CXCR5-expressing colon cancer cells; through the activation of PI3K/AKT/mTOR and Wnt/β-catenin signaling pathways [ 112 , 146 , 147 ].…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The significance of TME in mediating 5-FU drug resistance has also gained attention in recent years due to its crosstalk influence on tumor cell behavior. For instance, in one study, chemokine C-X-C motif ligand 13 (CXCL-13) is found highly-expressed in the TME of 5-FU-resistant colon cancer cells as well as in sera of 5-FU-resistant patients associated with worse clinical outcome [ 145 ]. Although the mechanism as to how CXCL-13 participates in 5-FU resistance was not stated, it is highly plausible that resistance is achieved through piggybacking the same pathways responsible in promoting tumor growth, migration, and invasion in CXCR5-expressing colon cancer cells; through the activation of PI3K/AKT/mTOR and Wnt/β-catenin signaling pathways [ 112 , 146 , 147 ].…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
“…It has been established that TILs are involved in chemotherapy response as elevated levels of chemokine CXCL-13 is determined in sera of 5-FU-resistant patients [ 145 ]. Knockdown of CXCL-13 resulted in re-sensitization of tumor cells with a significant increase in the number of B-cell infiltrating into the tumor cells.…”
Section: Reversal Strategiesmentioning
confidence: 99%
“…Ren et al demonstrated CXCR3-mediated AMPK signaling pathway contributed to metabolic alteration during the chemoresistance to agent-sorafenib in hepatocellular carcinoma [ 18 ]. Zhang et al identified CXCL13 was involved in 5-Fu resistance in colorectal cancer [ 19 ]. These studies suggested that chemokines and their receptors might be potential novel therapeutic targets of cancer chemoresistance.…”
Section: Backgroundsmentioning
confidence: 99%
“…Zhang Guolin et al identi ed CXCL13 was involved in 5-Fu resistance in colorectal cancer [20]. These studies suggested that chemokines and their receptors might be potential novel therapeutic targets of cancer chemoresistance.…”
Section: Backgroundsmentioning
confidence: 99%